The Role of KKN Students in Raising Environmental Awareness among Students at SDN 10 Kamang Baru - Amin, Muhammad; Novita , Yesi; Oktari , Rezi; Nabilah, Fadhillatun; Safrianti, Riska; Fictoria, Nur Hamizza (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
Environmental awareness needs to be instilled early in elementary school students as part of character education. However, many students still show a lack of concern for their surroundings, such as littering, neglecting cleanliness, and having limited knowledge about environmental conservation. In this context, Community Service Program (KKN) students play a vital role in supporting schools to foster environmental values through various educational programs. This study aims to describe the role of KKN students in increasing environmental awareness among students at SDN 10 Kamang Baru. This research employs a descriptive qualitative approach, with data collected through observation, interviews, and documentation. The informants include KKN students, supervising teachers, and students from grades IV to VI who were actively involved in environmental activities. Data were analyzed using Miles and Huberman's interactive model, which consists of data reduction, data display, and conclusion drawing. The results show that KKN students acted as facilitators, motivators, and educators in raising students’ environmental awareness. Activities conducted included environmental education campaigns, waste recycling projects, school greening, and class cleanliness competitions. Student participation significantly increased, as evidenced by improved behaviors in maintaining a clean and organized school environment. It can be concluded that the involvement of KKN students had a positive impact on shaping students’ environmental attitudes. Interactive and engaging programs proved effective in fostering environmental awareness from an early age. Similar initiatives are encouraged to be developed sustainably in other elementary schools.